Technical Aspects and Considerations of Meso-Rex Bypass Following Liver Transplantation With Left Lateral Segment Grafts: Case Report and Review of the Literature - Dalzell, Christina; Vargas, Paola A.; Soltys, Kyle; Di Paola, Frank; Mazariegos, George; Goldaracena, Nicolas (Frontiers in Pediatrics, 2022)
In pediatric patients with extrahepatic portal vein obstruction and complications of portal hypertension, but with normal liver function, a meso-Rex bypass (MRB) connecting the superior mesenteric vein to the intrahepatic left portal is the favored surgical management. Pediatric patients with a history of a partial liver transplant (LT), especially living donors, are at greater risk for portal vein complications. Hence, an adequate knowledge of this technique and its additional challenges in the post-LT patient setting is crucial. We provide an overview of the available literature on technical aspects for an MRB post-LT. Preoperative considerations are highlighted, along with intraoperative considerations and postoperative management. Special attention is given to the even-more-demanding aspect of performing an MRB post-liver transplantation with a left lateral segment. Surgical alternatives are also discussed. In addition, we report here a unique case in which this surgical technique was performed on a complex pediatric patient with a history of a living-donor LT with a left lateral segment graft over a decade ago.